Fostering human development through engineering and technology education - Barak, Moshe; Hacker, Michael (International technology education studies, 2011)
Fostering Human Development Through Engineering and Technology Education (ETE) is a collaborative work offered to students, scholars, researchers, decision-makers, curriculum developers, and educators interested in the rich learning opportunities afforded by engineering and technology education. This book provides perspective about the roles ETE might uniquely play in applying contemporary pedagogical practices to enhance students' intellectual, cognitive, and social skills in the service of promoting equitable and sustainable human development. Education about engineering and technology has become an imperative for all people due to the exponential rate of technological change, the impact of globalization on culture and economy, and the essential contributions engineering and technology make in addressing global and environmental challenges. Many of today's students wish to use their education to influence the future, and school-based engineering and technology education programs meet the needs of these ?millennial students? who are civic-minded, team-oriented, and want to make a difference. Therefore, support has been rapidly increasing for the establishment of school-based engineering and technology education (ETE) programs in many countries across the globe. Chapters in this book provide discussion about dimensions of learning; capabilities, concepts and skills for third millennial learners; culturally relevant learning through ETE; and the promise of new pedagogies such as gaming and other project-based learning approaches in our digitally connected world. The author team includes renowned educational theorists, cognitive scientists, scientists and engineers, instructional designers, expert practitioners, and researchers who have coalesced best practice and contemporary thought from seven countries.